Didactic intervention for the extraction and quantification of steroids in urine - Angulo, Diego Hernando; Casas, Jaime Augusto; Cipagauta, Edna Carolina; Aparicio, David Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article describes a didactic strategy for teaching a miniaturized solid-phase extractionmethod in the context of laboratory practical training [LPT]. It is based on the students’previous imaginaries in order to generate conceptual changes and promote meaningful learning through a few laboratory sessions. This article will report on the experience of combining the use of a sample preparation technique—PT-SPE—with a didactic intervention exercise for the improvement of procedural skills. We present the results of the application of LPT in the multi-determination of three steroids in urine samples using HPLC-DAD-PT-C18-SPE, which show adequate recovery rates and validation parameters. The results of the intervention show improvement of skills related to solid-phase extraction methods. It is concluded that there were conceptual changes in analytical processes, an adequate familiarization with new sample preparation methodologies, a significant increase in chemical vocabulary,and understanding of concepts, along with the application of lower-order cognitive processes to the enhancement of higher-order cognitive skills.